Management of Hybrid Renewable Energy Systems Using Differential Hybrid Petri Nets - Fohoue-Tchendjou, Kennedy; Kamla, Vivient Corneille; Bitjoka, Laurent (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Investigations in this paper concern management of Hybrid Renewable Energy systems. To achieve it, a supervisory system based on hybrid systems concept is designed, in order to ensure power flow between energy generators (solar panel and pico-hydroelectric), batteries and load. Differential Hybrid Petri Net is used to model the proposed supervisory and simulations are made in Matlab environment. Results obtained present a good performance criteria Loss of Power Supply Probability, and this show the effectiveness of our approach in the coordination of HREs components during the energy sharing process by reducing load shedding in microgrid system.